Quantum Synchronization for Multi Variable Packet Switching Security - K. Mitsophonsiri; S. Punthawanunt; S. Mitatha; P.P. Yupapin (My University, 2011)
We propose a new technique of signal synchronization using the correlated photon and a quantum processor, which can be performed incorporating in the communication link. The advantage is that data identification can be transmitted associating with the information data, whereas the synchronous key can be provided between Alice and Bob by using the dark solution tail(array) to form the quantum bits(qubits) via the quantum processor. In this paper, the dark soliton array is used to form the multi variable packet switching, which can be used to increase the communication capacity, whereas the security of data can be performed by the secret codes. Moreover, the secret codes can also be used to form the data identification which is known as signal (data) synchronization.
Keywords: Quantum Information and Cryptography